1993
DOI: 10.1088/0268-1242/8/10/013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic circular dichroism of a vanadium impurity in 6H-silicon carbide

Abstract: The magnetic circular dichroism of the absorption ( M C O ~) of Vi: in GH-silicon carbide shows a strong temperature dependence. Within a crystal field approach the MCOA and g-factors of the hexagonal site defect could be explained, whereas the situation is more complicated for both quasi-cubic site defects owing to a dynamical Jahn-Teller effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Recent studies using chromium, molybdenum, and vanadium in silicon carbide (SiC) have shown that they may be equally relevant for quantum applications, combining both brightness and (near-)telecom emission in a technologically mature material (14)(15)(16). Among these ions, vanadium V 4+ is the only fully telecom transition metal emitter, covering the entire O-band spectrum (1278 to 1388 nm), depending on its substitutional silicon site in the 4H and 6H polytypes of SiC (17)(18)(19). Although V has been studied for decades for compensating SiC crystals, critical questions remain regarding properties for quantum applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using chromium, molybdenum, and vanadium in silicon carbide (SiC) have shown that they may be equally relevant for quantum applications, combining both brightness and (near-)telecom emission in a technologically mature material (14)(15)(16). Among these ions, vanadium V 4+ is the only fully telecom transition metal emitter, covering the entire O-band spectrum (1278 to 1388 nm), depending on its substitutional silicon site in the 4H and 6H polytypes of SiC (17)(18)(19). Although V has been studied for decades for compensating SiC crystals, critical questions remain regarding properties for quantum applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, highly anisotropic interaction with magnetic field governed by the corresponding g-tensors has been observed or tentatively proposed for these KD systems [6,7], however the underlying physics has not been understood so far. Here we note that, although parallel component (g ) of g-tensor was thoroughly studied for V in 6H SiC by invoking crystal field theory, the emerging strong electron-phonon coupling is not included [2,[8][9][10][11] or considered as minor effect [1]. The strong anisotropy in g-tensor can be described by an effective Hamiltonian and pseudospins in which parameters cannot be predicted by applying simple models, and rather fitting procedure to known experimental data was applied.…”
mentioning
confidence: 99%
“…splitting [16]. At the hexagonal sites in SiC the rotational symmetry of the potential of the donor is perturbed the most, probably by a crystal field [17]. The more intense the E-type admixture into the 1s(A 1 ) ground state, the more does the A 1 state approach the E state within the band gap.…”
Section: Resultsmentioning
confidence: 99%